Comparative Study of Corrosion Inhibition of Commiphora caudata and Digera muricata for Mild Steel in 1 M HCl Solution - Aejitha, S.; Kasthuri, P.K.; Geethamani, P. (Asian Journal of Chemistry, 2015)
Commiphora caudata and Digera muricata extracts as corrosion inhibitors for mild steel in 1 M HCl were studied by weight loss and surface analysis techniques. It showed that both plant extracts inhibited the mild steel corrosion. Inhibition efficiency increased with increasing inhibitor concentration and temperature which suggested that the chemical mechanism. The inhibitors adsorbed onto the mild steel surface followed Langmuir adsorption isotherm. The surface morphology of mild steel showed that the addition of the extract reduces the mild steel corrosion.